Застосування методів механіки руйнування матеріалів для оцінювання міцності зварних з'єднань - Панасюк, В.В. (Автоматическая сварка, 2008)
The development of the methods of welds strength and durability assessment are the most actual trends in the science about materials strength. It is known that the state of material in the zone of joint weld differs from the state of the material that is joined by certain welding technologies. There are always different damages in the zone of the joint weld-defects, residual stresses that should be taken into consideration while calculating strength and durability of welded structures. The synthesis of some investigations on the influence of mentioned factors on strength and durability of welds using the concepts of up-to-date fracture mechanics of cracked solids (fracture mechanics) are given below.